O mundo na Igreja e a Igreja no mundo: reflexões sobre o Concílio Vaticano II e a modernidade - Contiero, Tiago Tadeu (2018)
This thesis aims at the Pastoral Constitution Gaudium et spes and seeks to understand how it contributed to the internal secularization of Catholicism, changing the way the Catholic Church relates to the modern world. The subject is shown relevant in so far as the document has recently completed its fifty years and is still little studied even by the Catholic hierarchy. At the same time, it is important to try to understand not only the acceptance of secularization but also how the tumultuous relationship between Church and modernity has taken place. We proceed from the hypothesis that every condemnation made by the ecclesiastical magisterium against the modern world loses its relevance with Gaudium et spes, since it brings within it the acceptance of modernity as being positive even for the Catholic Church. The research consists of a bibliographical analysis based not only on the prominent authors who have already worked on the theme, but also on primary sources such as diaries of Conciliar Fathers and the Constitution itself, which makes a greater contribution to the studies on the Council and the Pastoral Constitution. With the development of the research, we believe that Gaudium et spes followed in the opposite direction to the teaching that preceded it and, therefore, was responsible for the establishment of a new, essentially secular, Catholic imaginary